Netoscope: A New Black Box Through Which the Russian Government Controls Content Dissemination? - Sivetc Liudmila; Wijermars Mariëlle (Research Centre for East European Studies Publications Department, 2022)
Russia has increasingly adopted policies that leverage the power of private infrastructure owners, including algorithmic gatekeepers, to achieve more effective, but less easily perceptible, control over online content dissemination. This article analyzes the Netoscope project, which has compiled a database of Russian domain names suspected of malware, botnet or phishing activities. Within the framework of this project, federal censor Roskomnadzor cooperates with Yandex (which downgrades listed domains in its search results), Kaspersky, and foreign partners. The article concludes that non-transparency creates possibilities for misuse of the project.